2011
DOI: 10.1590/s1806-37132011000400008
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da terminação precoce da expiração nos parâmetros espirométricos em crianças pré-escolares saudáveis

Abstract: Objective: To evaluate the acceptability and reproducibility of spirometry in preschool children; to estimate the effect size of early termination of exhalation (ETE) on FVC, FEV 1 and FEV 0.5 ; and to evaluate the validity of FEV 0.5 in curves with ETE. Methods: Spirometric data were obtained from 240 healthy preschool children, who were selected by simple sampling. On the basis of the best curve from each child according to the end of exhalation, three groups were formed: no ETE (nETE); ETE and flow ≤ 10% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Given that spirometry is a low-cost and noninvasive test, and given that several studies 7 , 8 , 10 , 12 - 14 have demonstrated that preschool children can perform acceptable and reproducible FEV 0.5 and FEV 0.75 measurements, there is a need to determine bronchodilator response cut-off points for children in this age group so that spirometry can be used in daily clinical practice. Only two studies 18 , 19 have assessed bronchodilator response using spirometry exclusively in preschool children.…”
Section: Introductionmentioning
confidence: 99%
“…Given that spirometry is a low-cost and noninvasive test, and given that several studies 7 , 8 , 10 , 12 - 14 have demonstrated that preschool children can perform acceptable and reproducible FEV 0.5 and FEV 0.75 measurements, there is a need to determine bronchodilator response cut-off points for children in this age group so that spirometry can be used in daily clinical practice. Only two studies 18 , 19 have assessed bronchodilator response using spirometry exclusively in preschool children.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that ATS-DLD-78 can be utilised in multicultural settings in the translated questionnaire, with validation studies of the translated Sindhi, Portuguese, Urdu, French, Chinese, Norwegian, Thai, Hausa, Japanese, and Zulu versions showing considerable consistency across cultures [17][18][19][20][21][22][23][24][25][26][27] . As a result, the American Thoracic Society Division of Lung Disease questionnaire (ATS-DLD-78A) is an established method for evaluating and detecting respiratory system warning indicators in the investigated population globally.…”
Section: Introductionmentioning
confidence: 99%